2022
DOI: 10.1017/s0714980822000241
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Built Environment and Older Adults’ Activity: A Systematic Review

Abstract: Although the physical environment can influence people’s activity, there are few knowledge syntheses for indoor environments and older adults’ daily life routines. Therefore, we conducted a systematic review of peer-reviewed evidence to inform future research and practice. Inclusion criteria were studies with any research designs, across all years and languages focused on older adults 60 years of age or more, on physical activity/sedentary behaviour and the indoor environment. After searching five databases, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…There were 96 reviews assessed for full-text eligibility, and a further 93 documents were excluded for reasons including unspecified age categories, non-systematic reviews, incorrect population, and non-BE interventions and exposures. Several systematic reviews in particular were excluded because they did not report a summary/synthesis of findings across studies for older adults [45][46][47], did not report a summary of the quantitative findings specifically [23], or did not meet the criteria of a systematic review [48,49]. Ultimately, three reviews met the inclusion criteria [42,50,51].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 96 reviews assessed for full-text eligibility, and a further 93 documents were excluded for reasons including unspecified age categories, non-systematic reviews, incorrect population, and non-BE interventions and exposures. Several systematic reviews in particular were excluded because they did not report a summary/synthesis of findings across studies for older adults [45][46][47], did not report a summary of the quantitative findings specifically [23], or did not meet the criteria of a systematic review [48,49]. Ultimately, three reviews met the inclusion criteria [42,50,51].…”
Section: Resultsmentioning
confidence: 99%
“…As many older adults have a fear of falls from being active outdoors, especially in winter climates, having safe and accessible spaces to be active indoors such as in the hallways of apartments and malls are particularly important [23,24]. A recent review of 26 qualitative and quantitative studies [23] reported BE factors at three levels being associated with PA in older adults, including campus (e.g., aesthetics, recreation amenities), building (e.g., ground-level housing, private dwellings), and fixtures (e.g., indoor hallways, ramps, accessible stairwells). Thus, more high-quality research is needed on the potential role of indoor environments in the promotion and facilitation of PA in older adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation